ФОРМУВАННЯ ВХІДНОГО СТРУМУ МАТРИЧНОГО ПЕРЕТВОРЮВАЧА В УМОВАХ СПОТВОРЕНЬ НАПРУГИ МЕРЕЖІ ЖИВЛЕННЯ - Михальський , В.М.; Соболєв, В.М.; Чопик , В.В.; Шаповал , І.А.; Артеменко, М.Ю. (Інститут електродинаміки НАН України, Київ, 2016)
The matrix converter (MC) control methods based on MC input reactive power control algorithm, which aims to improve the quality of the MC input currents under conditions of nonsinusoidal voltages of the power network have been developed and studied. With this purpose, variants of setting the direction of the input current space vector relative to the input voltage space vector by appropriate regulation of the reactive component of the current have been considered. The simulation showed the effectiveness of the proposed approach to improve the quality of the MC input currents.  References 7, table 1, figures 2.